White Oyster Mushrooms (Pleurotus ostreatus) Cultivation by Log and Twigs Rubber, Leucaena, Randu, and Balsa - Elis Nina Herliyana; Abdul Muhyi (Jurnal Silvikultur Tropika, 2023)
Waste high fells form a log and twig wood type Leucaena (Leucaena leucocephala), rubber (Hevea brasiliensis), randu (Ceiba pentandra), and balsa (Ochroma bicolor) can be used as a medium cultivation of Oyster Mushrooms (Pleurotus ostreatus) to increase the value added of these four types of wood. The research aims to analyze the potential for the cultivation of Oyster Mushrooms white on media log and twig four types of wood, the nutrient content of mushrooms, and the appropriateness of business. The reserch used a completely randomized design (CRD) with 9 single factorial on media treatment of logs and twigs of four kindsdifferent wood; and baglog from sawdust as control. The results showed the average wet weight of fruiting bodies on rubber wood and lamtoro (heavy wood) in both the media logs and twigs , reaching 213 grams and is not significantly different from the control (262 grams) , but it is larger than other types of wood cottonwoods and balsa(light wood) which is, reaching only 130 grams. The efficiency of biological media from all kinds of wood twigs higher (29.6-36 %) and significantly different than logs (11-20.5 %). Vegetative phase on media of logs and twigs randu is faster (14 days) than other media and not significantly different. Generative phase (reproductive) kapok’s logs (62 days) and the branches (44 days) is longer and significantly different than other treatments. White Oyster Mushrooms nutritional content of all media types are quite good and worthy of consumption. White oyster mushroom cultivation using media log and twig are fit enough developed. Keywords: heavy wood, light wood, cultivation of white oyster mushroom, nutritional content